2014
DOI: 10.1111/joim.12232
|View full text |Cite
|
Sign up to set email alerts
|

The fibroblast growth factor‐23 and Vitamin D emerge as nontraditional risk factors and may affect cardiovascular risk

Abstract: Objectives. Fibroblast growth factor-23 (FGF-23) and vitamin D are hormones involved in phosphate homoeostasis. They also directly influence cardiomyocyte hypertrophy. We examined whether the relationships between levels of vitamin D or FGF-23, cardiac phenotype and outcome were independent of established cardiac biomarkers in a large cohort of community-dwelling elderly subjects.Design and Setting. Plasma levels of FGF-23 and vitamin D were measured in 1851 men and women (65-84 years) resident in the Lazio re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 50 publications
(81 reference statements)
1
35
0
Order By: Relevance
“…Hence, a total of 11 studies (12 articles) (65,019 participants) were eventually included in the meta-analysis; 7 studies (45,956 participants) for cardiovascular mortality [15,17,2125] and 10 studies (48,679 participants) for all-cause mortality. [15,17,18,2224,2629] Five studies reported HRs related to cardiac troponin T levels, [17,18,2123,26] and another 5 studies reported on cardiac troponin I levels. [15,24,25,2729] Clinical and demographic characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a total of 11 studies (12 articles) (65,019 participants) were eventually included in the meta-analysis; 7 studies (45,956 participants) for cardiovascular mortality [15,17,2125] and 10 studies (48,679 participants) for all-cause mortality. [15,17,18,2224,2629] Five studies reported HRs related to cardiac troponin T levels, [17,18,2123,26] and another 5 studies reported on cardiac troponin I levels. [15,24,25,2729] Clinical and demographic characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…According to the EPHPP quality assessment tool, [13] 1 study was of high methodological quality, [27] 8 studies were of moderate quality, [17,18,2125,28,29] and 2 studies were of low methodological quality. [15,26] The global rating “weak” for study quality was due to lack of information about subject inclusion, study withdrawals, and dropouts. To ascertain vital status, studies used death registries (n = 5), [17,22,24,26,29] medical records (n = 3), [18,21,27,28] the combination of medical records and death registries (n = 2), [15,25] and the combination of interviews, medical records, and a death register (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is a fatsoluble vitamin responsible for calcium and phosphorus homeostasis (88,89). Vitamin D deficiency has been previously associated with poorer neuropsychological function, metabolic syndrome, arrhythmias and coronary artery disease, and shares a complex interplay with other cardiovascular risk factors (88)(89)(90)(91)(92)(93). Numerous studies hypothesized that low levels of Vitamin D are inversely associated with cardiovascular disease and cardiac aging, however evidences and data from large clinical trials are limited (94)(95)(96).…”
Section: Vitamin Dmentioning
confidence: 99%
“…Studies have also shown a strong association between higher FGF 23 levels and left ventricular hypertrophy[32][33][34][35][36][37] with an increased risk for congestive heart failure. Masson et al evaluated Italian patients and demonstrated that high FGF 23 levels were independently associated with higher LV mass index and mortality after adjusting for other risk factors 38. The mortality risk related to elevated FGF 23 levels could be additive when combined with mortality risk from hyperphosphatemia, which may justify the argument that treatment of hyperphosphatemia needs to be aggressive and should begin early in CKD to prevent the rise in FGF 23 levels.The careful control of phosphorus early in CKD, possibly monitored by FGF 23 levels could potentially lower the risk of development of secondary hyperparathyroidism and the associated adverse effects of mineral and bone disease.…”
mentioning
confidence: 99%